Direct and Rapid Detection and Quantification of Oenococcus oeni Cells in Wine by Cells-LAMP and Cells-qLAMP - Soares-Santos, Verónica; Pardo, Isabel; Ferrer, Sergi (Frontiers in Microbiology, 2018)
Fast detection and enumeration of Oenococcus oeni in winemaking are necessary to determine whether malolactic fermentation (MLF) is likely to be performed or not, and to decide if the use of a commercial starter is needed. In other wines, however, performing MLF can be detrimental for wine and should be avoided. The traditional identification and quantification of this bacteria in wine-related matrices require up to 14 days to yield results, which can be a very long time to perform possible enological operations. Loop-mediated isothermal amplification (LAMP) is a novel culture-independent technique that amplifies nucleic acid sequences under isothermal conditions with high specificity and efficiency in less than 1 h with inexpensive equipment. We designed LAMP primers for the specific detection and quantification of O. oeni cells. The developed LAMP method allows O. oeni to be detected directly from both grape musts and wines within 1 h from the time that the LAMP reaction begins, and without DNA extraction and purification requirements. The high sensitivity of LAMP methodology is achieved by previous mechanical cells lysis with no further purification by detecting one single cell per reaction in culture media, and in white/red grape musts and wines by avoiding reaction inhibition by ethanol, polyphenols and other wine inhibitors. Cells can be concentrated prior to the LAMP reaction to further increase this sensitivity. Moreover, the LAMP method does not require expensive equipment and can be easily operated. The developed method is both economic and fast and offers high sensitivity and specificity